First description in Europe of the emergence of Enterococcus faecium ST117 carrying both vanA and vanB genes, isolated in Greece. (December 2017) - Papagiannitsis, C.C.; Malli, E.; Florou, Z.; Medvecky, M.; Sarrou, S.; Hrabak, J.; Petinaki, E.
Highlights: First report in Europe (Greece) of a ST117 Enterococcus faecium carrying both vanA and vanB genes. vanA was carried on a plasmid exhibiting high similarity to pA6981 previously characterised from E. gallinarum A6981. vanB was part of a Tn 1549 -like transposon integrated into the chromosome. Full resistance to vancomycin and teicoplanin (MICs = 256 mg/L correlated with the presence of intact vanZ and vanS genes). Abstract: Objectives: An Enterococcus faecium isolate (Efa-125) carrying both the vanA and vanB genes was recovered from a patient with bacteraemia treated in a Greek hospital. Since this is the first description in Europe of E. faecium carrying both vanA and vanB genes, the isolate was further studied. Methods: Susceptibility to several antibiotics was determined using the VITEK ® 2 automated system. The isolate was typed by multilocus sequence typing (MLST). To define the genetic units of the vanA and vanB genes, the plasmid content of Efa-125 was analysed by pulsed-field gel electrophoresis (PFGE) of total DNA digested with S1 nuclease followed by hybridisation with digoxigenin-labelled vanA and vanB probes. In addition, plasmids and chromosomes were sequenced using the Illumina MiSeq platform. Results: E. faecium Efa-125 belonged to ST117 and expressed resistance both to vancomycin and teicoplanin, with minimum inhibitory concentrations (MICs) for both of 256 mg/L. The vanA gene was carried on a 29 320-bp plasmid exhibiting high similarity to pA6981 previously characterised from Enterococcus gallinarum A6981, whereas vanB was part of a Tn 1549 -like transposon integrated into the chromosome. Expression of the VanA phenotype was correlated with the presence of intact van Z and vanS genes. Conclusions: This is the first detection in Greece of vanA–vanB genotype/VanA phenotype E. faecium and indicates an evolving epidemiology of vancomycin-resistant enterococci.